Electronic structure of formamidinium ions in lead triiodide perovskites. Issue 9 (16th August 2016) - Shen, Pengfei; Nie, Kaiqi; Sun, Xuhui; Liu, Lijia; McLeod, John A.
Abstract : Perovskite formamidinium lead triiodide (FAPbI3 ) is a very promising photovoltaic material. Unfortunately, perovskite FAPbI3 converts to a hexagonal phase at ambient conditions. Herein we study the electronic structure of both perovskite and hexagonal FAPbI3 films using soft X‐ray absorption near edge structure (XANES) and density functional theory. We find that the C and N 2p states of FA hybridize with the Pb, I states at the conduction band minimum in hexagonal, but not perovskite, FAPbI3 . We also demonstrate that C K‐edge XANES can be used to investigate shifts in the valence band in other organic‐inorganic hybrid perovskites.Graphical summary of the electronic structure and C K‐edge XANES in both perovskite and hexagonal FAPbI3 highlighting our findings. Abstract : Perovskite formamidinium lead triiodide (FAPbI3 ) is a promising photovoltaic, but hexagonal FAPbI3 is more stable at ambient conditions. The authors use soft X‐ray absorption spectroscopy and density functional theory to study both phases. Their findings elucidate the phase change, and it is shown how soft X‐ray absorption spectroscopy is to obtain important details of the electronic structure of other organic–inorganic hybrid perovskites.